2008
DOI: 10.1017/s1751731108002437
|View full text |Cite
|
Sign up to set email alerts
|

Effects of meal-time feeding and protein restriction on walking ability and some bone and carcass properties in broilers

Abstract: This experiment was designed to investigate the effects of meal-time feeding and protein restriction on performance, gait score (GS) and carcass and bone traits in broilers. A total of 420 1-day-old chicks were wing banded and randomly distributed into 21 pens with 20 chicks each. At 7 days of age, chicks were weighed and randomly assigned to one of the three treatments: (1) control (C) feed (23.02% crude protein (CP)) was available ad libitum; (2) meal-time feeding (MF); control feed was available from 0100 t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…Individual samples were placed inside polyethylene bags and then added to a water bath at 80 °C for 30 min or until the temperature of 72 or 75 °C was achieved, followed by a 30‐min cooling period. The samples were removed from the bags, dried with paper and then weighed (Konca et al., ). The weight loss after cooking was expressed as a percentage of initial weight.…”
Section: Methodsmentioning
confidence: 99%
“…Individual samples were placed inside polyethylene bags and then added to a water bath at 80 °C for 30 min or until the temperature of 72 or 75 °C was achieved, followed by a 30‐min cooling period. The samples were removed from the bags, dried with paper and then weighed (Konca et al., ). The weight loss after cooking was expressed as a percentage of initial weight.…”
Section: Methodsmentioning
confidence: 99%
“…In addition, these researchers showed that birds fed fewer meals per day had less TD and better walking ability. However, Konca et al (2008) reported that meal-time feeding and protein restriction had no significant impact on GS of broilers at day 45 of age.…”
Section: Leg Weaknessmentioning
confidence: 97%
“…Therefore, the restriction of water consumption also decreases feed intake (Viola et al 2009). Early feed restriction has successfully been used by many researchers to lower the early growth rate of broilers and its favorable effects on carcass fat contents, feed efficiency (Nielsen et al 2003;Khetani et al 2009), total mortality (UrdanetaRincon and Leeson 2002), metabolic diseases (Lippens et al 2000), and leg health (Konca et al 2008) are fairly established. However, there is little or limited information concerning the application of early-age water restriction as a practical approach to induce feed restriction and its impact on broilers performance, immunity, and leg health.…”
Section: Introductionmentioning
confidence: 99%